Street art by Shilo Shiv Suleman on the theme of water - Ghosh, Ayan (2023)
The northeast lane to Banganga Tank has a contemporary wall mural created by award-winning installation artist Shilo Shiv Suleman in 2021. Titled Pyaas, it draws attention to the origin myth of the Banganga Tank. The theme alludes to the role of women and the importance of water in the daily life and livelihoods of the local residents at Walkeshwar.